2003
DOI: 10.1046/j.1460-9568.2003.02892.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated methylphenidate treatment in adolescent rats alters gene regulation in the striatum

Abstract: Methylphenidate is a psychostimulant which inhibits the dopamine transporter and produces dopamine overflow in the striatum, similar to the effects of cocaine. Excessive dopamine action is often associated with changes in gene expression in dopamine-receptive neurons. Little is known about methylphenidate's effects on gene regulation. We investigated whether a methylphenidate treatment regimen known to produce behavioural changes would alter gene expression in the striatum. Using in situ hybridization histoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

22
98
3
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(124 citation statements)
references
References 68 publications
(112 reference statements)
22
98
3
1
Order By: Relevance
“…Our results demonstrate that both acute molecular effects of cocaine, as well as neuroadaptive changes after repeated cocaine treatment are maximal in specific dorsal striatal sectors of Online publication: 28 October 2005 at http://www.acnp.org/citations/ Npp102805050423/default.pdf the middle to caudal striatum (Willuhn et al, 2003). A principally similar topography was found for gene regulation effects of acute and repeated treatment with the psychostimulants methylphenidate (Brandon and Steiner, 2003;Yano and Steiner, 2005a, b) and amphetamine (Meredith and Steiner, 2006). In all of these studies, the most affected striatal sectors are parts of the sensorimotor striatum that receive convergent cortical inputs predominantly from the medial agranular (premotor) and sensorimotor cortex (see Willuhn et al, 2003).…”
Section: Introductionsupporting
confidence: 66%
“…Our results demonstrate that both acute molecular effects of cocaine, as well as neuroadaptive changes after repeated cocaine treatment are maximal in specific dorsal striatal sectors of Online publication: 28 October 2005 at http://www.acnp.org/citations/ Npp102805050423/default.pdf the middle to caudal striatum (Willuhn et al, 2003). A principally similar topography was found for gene regulation effects of acute and repeated treatment with the psychostimulants methylphenidate (Brandon and Steiner, 2003;Yano and Steiner, 2005a, b) and amphetamine (Meredith and Steiner, 2006). In all of these studies, the most affected striatal sectors are parts of the sensorimotor striatum that receive convergent cortical inputs predominantly from the medial agranular (premotor) and sensorimotor cortex (see Willuhn et al, 2003).…”
Section: Introductionsupporting
confidence: 66%
“…Our results showed that repeated treatment with 10 mg/kg once daily for 7 days produced increased expression of the neuropeptide dynorphin and attenuated the inducibility of immediate-early genes (c-fos, zif 268) and substance P in the striatum (Brandon and Steiner, 2003). These effects were principally similar to those of repeated cocaine and amphetamine treatments (see Brandon and Steiner, 2003;Willuhn et al, 2003, for discussion).…”
Section: Introductionsupporting
confidence: 62%
“…Our results showed that repeated treatment with 10 mg/kg once daily for 7 days produced increased expression of the neuropeptide dynorphin and attenuated the inducibility of immediate-early genes (c-fos, zif 268) and substance P in the striatum (Brandon and Steiner, 2003). These effects were principally similar to those of repeated cocaine and amphetamine treatments (see Brandon and Steiner, 2003;Willuhn et al, 2003, for discussion). Substance P and dynorphin are contained in neurons of the direct striatal output pathway (striatonigral neurons) (Gerfen and Young, 1988;Graybiel, 1990;Gerfen and Wilson, 1996), and our results thus suggested that repeated methylphenidate treatment produces molecular alterations in the direct pathway.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations